Application of adaptive notch filter for harmonics currents estimation - Tarek, M.; Mekhilef, Saad; Rahim, N.A. (2007)
Power system signals are often contaminated with harmonics and noise. It is preferable to determine these harmonics for analysis, control and design of power system devices and protection. This paper presents an efficient technique for harmonics current estimation based on adaptive notch filter (ANF). The proposed filter structure is tested, simulated and implemented in a digital signal processor (DSP) TMS320F2808. As an application, the proposed filter is used for controlling a hybrid active power filter (HAPF). The theoretical expectation are verified and demonstrated experimentally.